Ribosomal RNA kink-turn motif--a flexible molecular hinge - Rázga, Filip; Spackova, Nad'a; Réblova, Kamila; Koca, Jaroslav; Leontis, Neocles B; Sponer, Jirí (Journal of biomolecular structure & dynamics, 2004)
Ribosomal RNA K-turn motifs are asymmetric internal loops characterized by a sharp bend in the phosphodiester backbone resulting in "V" shaped structures, recurrently observed in ribosomes and showing a high degree of sequence conservation. We have carried out extended explicit solvent molecular dynamics simulations of selected K-turns, in order to investigate their intrinsic structural and dynamical properties. The simulations reveal an unprecedented dynamical flexibility of the K-turns around their X-ray geometries. The K-turns sample, on the nanosecond timescale, different conformational substates. The overall behavior of the simulations suggests that the sampled geometries are essentially isoenergetic and separated by minimal energy barriers. The nanosecond dynamics of isolated K-turns can be qualitatively considered as motion of two rigid helix stems controlled by a very flexible internal loop which then leads to substantial hinge-like motions between the two stems. This internal dynamics of K-turns is strikingly different for example from the bacterial 5S rRNA Loop E motif or BWYV frameshifting pseudoknot which appear to be rigid in the same type of simulations. Bistability and flexibility of K-turns was also suggested by several recent biochemical studies. Although the results of MD simulations should be considered as a qualitative picture of the K-turn dynamics due to force field and sampling limitations, the main advantage of the MD technique is its ability to investigate the region close to K-turn ribosomal-like geometries. This part of the conformational space is not well characterized by the solution experiments due to large-scale conformational changes seen in the experiments. We suggest that K-turns are well suited to act as flexible structural elements of ribosomal RNA. They can for example be involved in mediation of large-scale motions or they can allow a smooth assembling of the other parts of the ribosome.
Keywords: Models, Molecular; vodíková vazba; RNA, Archaeal; sekvence nukleotidů; Static Electricity; termodynamika; krystalografie rentgenová; vazebná místa; Crystallography, X-Ray; molekulární modely; Haloarcula marismortui; Binding Sites; statická elektřina; archeální RNA; RNA ribozomální; Thermodynamics; Base Sequence; voda; RNA, Ribosomal; konformace nukleové kyseliny; Hydrogen Bonding; Nucleic Acid Conformation; Water